2022
DOI: 10.5455/ajvs.127630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance Profile of Methicillin Resistant Staphylococcus aureus strains Isolated from Food Products and Food Handlers in Egypt

Abstract: The study aimed to determine the prevalence and phenotypic antimicrobial resistance pattern of Methicillin Resistant Staphylococcus aureus (MRSA) isolated from food products and food handlers at different retail outlets and superstores in Alexandria city, Egypt. A total of 100 food products including raw milk, Damietta cheese, beef burger, sausage, and chicken pane (20 of each) as well as 100 hand swabs were randomly collected from 100 food handlers and screened for the presence of MRSA using MRSA selective ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The PCR confirmed isolates were subjected to susceptibility testing using 8 antibiotics. This was performed by the Kirby-Bauer agar disk diffusion method on Mueller-Hinton according to [25]. The pure colonies were suspended in sterile normal saline, adjusted to 0.5 MacFarland standard before making a lawn on Mueller Hinton agar (Oxoid CM0337B) using sterile swab stick.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR confirmed isolates were subjected to susceptibility testing using 8 antibiotics. This was performed by the Kirby-Bauer agar disk diffusion method on Mueller-Hinton according to [25]. The pure colonies were suspended in sterile normal saline, adjusted to 0.5 MacFarland standard before making a lawn on Mueller Hinton agar (Oxoid CM0337B) using sterile swab stick.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…However, bacteria other than coagulase positive S. aureus were found in 20 (33.50%), while 15 samples (24.83%) of the samples did not exhibit bacterial growth (Table 2). Staphylococci are one of the most prevalent bacterial contaminants according to USFDA [2004] [25] reported that S. aureus is ubiquitous in nature and inhabits the mucous membranes and skin of most warm-blooded animals, including food animals and humans.…”
Section: Prevalence Of S Aureus Isolates Found In Rte Ponmo Samplesmentioning
confidence: 99%